Magnesium Limitation Leads to Transcriptional Down-Tuning of Auxin Synthesis, Transport, and Signaling in the Tomato Root - Ishfaq, Muhammad; Zhong, Yanting; Wang, Yongqi; Li, Xuexian (Frontiers in Plant Science, 2021)
Magnesium (Mg) deficiency is becoming a widespread limiting factor for crop production. How crops adapt to Mg limitation remains largely unclear at the molecular level. Using hydroponic-cultured tomato seedlings, we found that total Mg2+ content significantly decreased by ~80% under Mg limitation while K+ and Ca2+ concentrations increased. Phylogenetic analysis suggested that Mg transporters (MRS2/MGTs) constitute a previously uncharacterized 3-clade tree in planta with two rounds of asymmetric duplications, providing evolutionary evidence for further molecular investigation. In adaptation to internal Mg deficiency, the expression of six representative MGTs (two in the shoot and four in the root) was up-regulated in Mg-deficient plants. Contradictory to the transcriptional elevation of most of MGTs, Mg limitation resulted in the ~50% smaller root system. Auxin concentrations particularly decreased by ~23% in the Mg-deficient root, despite the enhanced accumulation of gibberellin, cytokinin, and ABA. In accordance with such auxin reduction was overall transcriptional down-regulation of thirteen genes controlling auxin biosynthesis (TAR/YUCs), transport (LAXs, PINs), and signaling (IAAs, ARFs). Together, systemic down-tuning of gene expression in the auxin signaling pathway under Mg limitation preconditions a smaller tomato root system, expectedly stimulating MGT transcription for Mg uptake or translocation.